(untitled) (Research, Society and Development, 2022)
Aeromonads are natural inhabitants of aquatic environments and may be associated with numerous infections in humans and animals. The human disease may range from self-limiting diarrhea to a more severe form. The pathogenesis of infections are multifactorial, because of their wide variety of virulence factors. This study aimed to evaluate virulence markers in Aeromonas isolates and determinate their virulence profiles. There were analyzed 120 strains of A. caviae (n = 57) and A. hydrophila (n = 63) from human, animal and environmental sources between 2008 and 2012. All isolates were examined to detect extracellular virulence enzymes by phenotypic activity and the presence of virulence genes hlyA, aerA, lip, gcat, ser, act, alt and exu by PCR. We observed more than 90% of positivity for at least one phenotypic virulence factors and all of them had at least two of the virulence genes measured. Among the virulence enzymes detected, the DNase was present in 93.33% of the isolates and hemolytic activity was detected in 62.5%. Collagenase and elastase were found in 13.33% and 10.83% of the strains, respectively. We found exu and gcat in 100% of the isolates, lip in 40.83%, aerA in 40.83%, hlyA in 40%, alt in 19.16%, act in 17.5% and ser in 11.66%. It was possible to observe different combinations of virulence factors between the isolates showing the multifactorial virulence among the isolates. The diversity of virulence profiles found in this study hint heterogeneity in clones circulating in our environment.